The knowledge, attitude and practice of local Sabahan in Malaysia on Sunda pangolin - Elsiey Ercy Jomes; Fred Tuh; Walter Lintangah; Jephte Sompud (ResearchGate, 2023)
Jomes EE, Tuh F, Lingtangah W, Sompud J. 2023. The knowledge, attitude and practice of local Sabahan in Malaysia on Sunda pangolin. Biodiversitas 24: 4702-4710. The IUCN Red List of Threatened Species listed Sunda pangolin (Manis javanica) as critically endangered and they remained among the most traded mammals and other pangolin species. In Sabah, various conservation works on this species have been conducted these past years through government and NGO works. Nevertheless, their population is still declining despite all the efforts. To date, little to nothing is known about the local perception regarding Sunda pangolin conservation. Therefore, through the Knowledge, Attitude, and Practice (KAP) approach, this study evaluates Sabahan’s awareness level regarding the Sunda pangolin conservation. A total of 109 Sabahan respondents were interviewed from all across Malaysia to investigate their perception of Sunda pangolin conservation. The KAP index score shows that respondents’ attitude toward Sunda pangolin conservation is the highest (93.34%), followed by Knowledge (81.15%) and Practice (79.63%), of which all three fall within good KAP score. They also agreed that spreading awareness and being proactive in supporting conservation work helps to prevent this species from extinction. Interestingly, the correlation analysis using Spearman rho’s coefficient shows a positive relationship between KA and education but not for Practice. Generally, Sabahans had a positive understanding of the Sunda pangolin’s current status and the legal information regarding this species. This research may help improve species conservation strategies, particularly in Sabah, Malaysia. There is an urgent need to improve the Sunda pangolin conservation program in the future. Factors that influence Practice need to be identified and scrutinized. Public awareness is not the only factor that needs to be considered for improvement in conservation works. More importantly, the people who work in the conservation field.